Accurate Modelling of Group Electrostatic Potential and Distributed Polarizability in Dipeptides. Issue 19 (11th September 2020) - Jabłuszewska, Angelika; Krawczuk, Anna; Dos Santos, Leonardo H. R.; Macchi, Piero
Abstract: Within the scope of accurate structure‐property correlations in biomolecules, this work investigates how conformations and electronic configurations of biologically relevant macromolecules affect their intermolecular potentials. With the purpose of testing the suitability of a simple and universal model, the dipeptides are made from the assembly of their building blocks, namely the amino acid residuals or, more finely tuned, the individual functional groups. The model makes use of functional‐group electrostatic potentials (GEP) and distributed polarizabilities (GDP), which enable an in depth analysis of the correlation between structural features and property build‐up. GEPs and GDPs are calculated for various conformers and protonation states of L‐alanyl‐L‐alanine, glycyl‐L‐alanine, L‐alanylglycine, and glycylglycine, which are prototypic molecules to model the pertinent functional groups. The model provides GEPs that reproduce the exact potential to an average accuracy of ca. 0.05 au. The good agreement between the properties estimated with the simple model and those calculated with state‐of‐the‐art quantum chemical methods encourages further testing of the predictive power of this model, simulating for example interaction energies and optoelectronic properties. Abstract : Electric properties of biomolecules from building blocks : The atomic or functional‐group electrostatic potential and distributed polarizability in dipeptides help to predict the electric properties of bio‐macromolecules from their structural subunits. By focusing on the peptide bond, the model takes advantage of a simple and transferable scheme to gain insight on how amino acid residuals ensemble to create proteins.